EKOSISTEM TEKNOLOGI PENDIDIKAN MASA DEPAN - Dedi Lazwardi; Rachmat Panca Putera; Sucipto (Jurnal Dinamika Pendidikan Islam, 2025)
Future educational technology ecosystem represents a transformative paradigm in learning through digital innovation and humanistic approaches. Research explores advanced technologies like artificial intelligence in creating adaptive and personalized learning environments. The study analyzes technology integration complexity, focusing on multidisciplinary collaboration and digital infrastructure development. It identifies key challenges, including digital divide and maintaining ethical dimensions in technological transformation.Findings demonstrate the need for a holistic approach beyond mere technology implementation. The primary goal is empowering individuals to address global challenges, emphasizing 21st-century skills and strong character development. Conclusions affirm the balance between technological innovation and human values in designing sustainable educational futures.